A Critical Review of the Common Fisheries Policy - Carsten Lynge Jensen (University of Southern Denmark, Department of Environmental and Business Economics (IME), 1999)
The paper embodies an evaluation of the fishery policy at EU level. The common fishery policy is designed to solve a complex set of problems that emerge in the sector. This embodies on the one hand that the fishery policy is directed towards objectives that have their offspring in different theoretical paradigms for conservation, rationalisation and the community. On the other hand, the common fishery policy is also accommodates to solve the conflicting interests of the Member States; for example the resource sharing. The analysis in the paper shows that the Common Fishery Policy is based on inconsistent objectives, which arise as a consequence of the attempt to formulate a policy that deals with mutually conflicting objectives at the same time. The paper takes its outline in describing elements in the historical process of the development of the common fisheries policy. It is found that the issue of equal or restricted access to the fish resource has had an important influence on the formulating of the historical policies as it is also has today. In the analysis of the current fishery policy the paper primarily places its focus on the elements of the policies for conservation, structure and control, their objectives and means. It is indicated that the implemented policies do not state solution that entirely prevents the distortions of overfishery and overcapitalisation present in the classical open access fishery. This is e.g. seen in the structural policy, where the Member States are not prevented from acting strategically in order to pursue their own interests. Moreover, the control policy shows that the EU has had difficulties in implementing a reliable policy, which would prevent the Member States from using the control policy in their own favour by implementing a laissez faire policy, and thereby indirectly benefit from their national fishing industries.
Keywords: 330; Common fishery policy; fisheries conflicts; conservation policy; structural policy; control policy; EU-Fischereipolitik